A micromammalian framework for the Quaternary of southern Africa - (:unkn) unknown (My University, 2024)
The study of micromammals holds a unique position in archeozoological and paleontological disciplines. Micromammals, defined as mammals weighing less than 500g, represent nearly 70% of mammalian diversity, making them an exceptionally varied group from ecological and evolutionary perspectives. Due to their small size, the collection of micromammal fossils requires labor-intensive and time-consuming sampling methods, involving fine sediment sieving and meticulous sorting of sieve residues. Moreover, the abundance of their remains within fossil assemblages from cave sites in southern Africa allows the use of robust statistical methods. Traditionally, the study of Cenozoic micromammals, especially rodents, finds three major applications in paleontology: biochronology, taxonomy, and paleoecology. For the South African Quaternary, these three applications provide valuable insights into human evolutionary history: biochronological studies serve as independent chronological tools to validate or complement numerical age estimates; taxonomic studies provide insights into the palaeobiodiversity and evolutionary history of organisms, shedding light on species diversification and migration over time; paleoenvironmental studies help elucidate the role of environmental pressures in hominin speciation, extinction, and adaptation. Today, scientific advances made in the past two decades allow researchers to overcome the methodological limitations that constrained microfaunal studies from southern African sites until recently. Molecular phylogenies enable better understanding of rodent systematics and biogeography. Methods of shape quantification, such as geometric morphometrics and deep learning, facilitate detailed morpho-anatomical comparative analyses for taxonomic and biochronological purposes. Statistical developments, including machine learning, enhance the study of the relationship between modern and fossil faunas and their environments. These methodological adv
Keywords: African Research